Analysis and Design of Nonlinear Control Systems - Cheng, Daizhan; Hu, Xiaoming; Shen, Tielong; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
"Analysis and Design of Nonlinear Control Systems" provides a comprehensive and up to date introduction to nonlinear control systems, including system analysis and major control design techniques. The book is self-contained, providing sufficient mathematical foundations for understanding the contents of each chapter. Scientists and engineers engaged in the field of Nonlinear Control Systems will find it an extremely useful handy reference book. Dr. Daizhan Cheng, a professor at Institute of Systems Science, Chinese Academy of Sciences, has been working on the control of nonlinear systems for over 30 years and is currently a Fellow of IEEE and a Fellow of IFAC, he is also the chairman of Technical Committee on Control Theory, Chinese Association of Automation.
Topological Space -- Differentiable Manifold -- Algebra, Lie Group and Lie Algebra -- Controllability and Observability -- Global Controllability of Affine Control Systems -- Stability and Stabilization -- Decoupling -- Input-Output Structure -- Linearization of Nonlinear Systems -- Design of Center Manifold -- Output Regulation -- Dissipative Systems -- L 2 -Gain Synthesis -- Switched Systems -- Discontinuous Dynamical Systems.
Keywords: Mathematics; Systems theory; Mathematics; Systems Theory, Control; Control